Trans-national cooperation: an asset in the Portuguese overseas trade. Foreigners operating in the Portuguese overseas trade, 1580-1590 - Ribeiro, Ana Sofia (2015)
This paper aims to discuss the role of foreign merchants, operating from Portugal, in the Portuguese overseas trade, during the first ten years of Iberian Union. The focus is not in products or routes, but in the mechanisms of association of such merchants. Iberian Union created a legal framework which prohibited the interference and trade of Portuguese agents in the Spanish Empire and vice-versa. Due to the imperialist wars of the Habsburgs, the Portuguese Empire also suffered from Dutch and English rivalry both in the Indic and in the Atlantic and also from the embargos of Dutch and English products and ships in Iberian ports. In such conjuncture, how did merchants related with each other? What was the impact of the political union of the Portuguese and Spanish crowns in trading associations? The used data sources are the notarial contracts of Lisbon for the same period. The paper highlights the role of Castilian merchants in the Portuguese trade, but it also stresses that Iberian partnerships have prevailed before 1580. The role of other merchants, such as Flemish/Dutch, Germans, Italians and French, is also considered. The paper discusses how and why did these merchants join in trans-national partnerships and what was their role in the Portuguese trade network at the time.